Persepsi Orang Tua tentang Pendidikan Seks Usia Dini dalam Konteks Edukasi Parenting di Kota Jambi - Bangsawan, Indra; Ridwan, Ridwan; Huda, Huda; Husin, Husin (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2025)
Parenting plays a crucial role in helping parents understand and apply child-rearing practices that align with each child’s unique characteristics. Parenting education provided to families in Jambi City, Jambi Province, is expected to enhance parental knowledge in childcare while also serving as an initial preventive measure against child abuse and domestic violence. This study aims to analyse parents’ perceptions of early childhood sex education. A qualitative approach with a descriptive-analytical design was employed, using observation, interviews, and documentation as data collection techniques. The findings reveal that Parenting education is a fundamental need for parents in shaping children’s character and supporting their development. Appropriate knowledge and skills in childcare are essential to address the challenges of an ever-changing era. Therefore, a holistic and systematic approach is required to strengthen parents’ understanding of effective Parenting concepts.